Genome-Wide Analysis of the Indispensable Role of Non-structural Proteins in the Replication of SARS-CoV-2 - Jin, Yunyun; Ouyang, Muzi; Yu, Ting; Zhuang, Jiaxin; Wang, Wenhao; Liu, Xue; Duan, Fangfang; Guo, Deyin; Peng, Xiaoxue; Pan, Ji-An (Frontiers in Microbiology, 2022)
Understanding the process of replication and transcription of SARS-CoV-2 is essential for antiviral strategy development. The replicase polyprotein is indispensable for viral replication. However, whether all nsps derived from the replicase polyprotein of SARS-CoV-2 are indispensable is not fully understood. In this study, we utilized the SARS-CoV-2 replicon as the system to investigate the role of each nsp in viral replication. We found that except for nsp16, all the nsp deletions drastically impair the replication of the replicon, and nsp14 could recover the replication deficiency caused by its deletion in the viral replicon. Due to the unsuccessful expressions of nsp1, nsp3, and nsp16, we could not draw a conclusion about their in trans-rescue functions. Our study provided a new angle to understand the role of each nsp in viral replication and transcription, helping the evaluation of nsps as the target for antiviral drug development.